In silico identification of promiscuous scaffolds as potential inhibitors of 1-deoxy-d-xylulose 5-phosphate reductoisomerase for treatment of Falciparum malaria - Abdul Wadood; Mehreen Ghufran; Syed Fahad Hassan; Huma Khan; Syed Sikandar Azam; Umer Rashid (Taylor & Francis Group, 2017)
Context: Malaria remains one of the prevalent infectious diseases worldwide. Plasmodium falciparum 1-deoxy-d-xylulose-5-phosphate reductoisomerase (PfDXR) plays a role in isoprenoid biosynthesis in the malaria parasite, making this parasite enzyme an attractive target for antimalarial drug design. Fosmidomycin is a promising DXR inhibitor, which showed safety as well as efficacy against Plasmodium falciparum malaria in clinical trials. However, due to its poor oral bioavailability and non-drug-like properties, the focus of medicinal chemists is to develop inhibitors with improved pharmacological properties. Objective: This study described the computational design of new and potent inhibitors for deoxyxylulose 5-phosphate reductoisomerase and the prediction of their pharmacokinetic and pharmacodynamic properties. Material and methods: A complex-based pharmacophore model was generated from the complex X-ray crystallographic structure of PfDXR using MOE (Molecular Operating Environment). Furthermore, MOE-Dock was used as docking software to predict the binding modes of hits and target enzyme. Results: Finally, 14 compounds were selected as new and potent inhibitors of PfDXR on the basis of pharmacophore mapping, docking score, binding energy and binding interactions with the active site residues of the target protein. The predicted pharmacokinetic properties showed improved permeability by efficiently crossing blood-brain barrier. While, in silico promiscuity binding data revealed that these hits also have the ability to bind with other P. falciparum drug targets. Discussion and conclusion: In conclusion, innovative scaffolds with novel modes of action, improved efficacy and acceptable physiochemical/pharmacokinetic properties were computationally identified.